PROFILE OF THE CLIENTELE ATTENDED BY THE NURSE IN THE MOTHER-AND-BABY EMBRACEMENT STRATEGY - Jéssica Lima Silva; Wânia Priscila Andrade de Melo; Renata Abreu Sá; Gláucia Cristina Lima da Silva; Nathália dos Santos Trindade; Maria Helena Nascimento Souza (Universidade Federal do Paraná, 2013)
This quantitative study of the descriptive-exploratory type aimed to identify socio-demographic and health characteristics of mothers and babies attended by nurses in the Mother-and-Baby Embracement Strategy in a primary health care unit in the city of Rio de Janeiro. The data was collected from 26 hospital records which had the Guide for Mother-and-Baby Embracement Consultation Activities protocol, in 2011. The data was analyzed using the Epi-infor 3.5.2 software. The results show that 61.3% of the women were in the age range 20 to 30 years old; 46.2% had had a normal birth; 7.7% had changes in the surgical scar and 11.5% had changes in their breasts. In relation to the new-borns, 50% were between 2 and 7 days old; the majority (96.2%) were being exclusively breast-fed, and 23.1% presented jaundice. It is concluded that knowledge of the profile of the clientele attended in the Mother-and-Baby Embracement, by the nurse, constitutes important support for carrying out health promotion measures which aim to reduce maternal and infant morbidity and mortality.